Towards an application of musharakah mutanaqisah principle in Islamic microfinance - Md Saad, Norma; Abdul Razak, Dzuljastri (Unimas, 2013)
This paper is aimed at explaining the application of musharakah mutanaqisah into a newly context of Islamic microfinance. The term Islamic microfinance is similar to that of conventional but it is varied in terms of Shariah principles used and the prohibition of interest in business operations. Further, microfinance institutions have been established in many developing countries to solve the problem of poverty. In muslim countries, Islamic microfinance can be a powerful tool to fight poverty if these institutions are managed in the right way. Islamic finance scholars have argued that the provision of equity based financing by Islamic financial institutions will facilitate toward achieving the Islamic socio-economic objectives which include social justice, economic growth, efficiency and stability. This paper illustrates that musharakah mutanaqisah, an equity based financing instrument, is better than debt-based financing because of its flexibility and end result in the ownership of assets on the part of the customer. The paper also highlights musharakah mutanaqisah as an innovative mode of financing and should be a preferred instrument of financing by Islamic microfinance institutions. Our study provides further evidence regarding the applicability of musharakah mutanaqisah into the context of microfinance, thus closing the research gaps. Limitation and potential future work are outlined to assist future researches in the area.